Visual Factors On Social Media Influence Youth Tourist Purchasing Decision: A Meta Analysis Review - Loh, Ngiik Hoon; Natasha, Rusdy Wong; Ahmad Azaini, Abdul Manaf (Aliva Global Research and Development, 2021)
The increasing trend of young tourists today is a global phenomenon due to the influence of social media and new technologies, as in the case of traveler’s destination choice and making a purchase decision. Short form video is another new trend such as TikTok, Instagram and Facebook platform which are growing fastest worldwide. Due to the fact that youth tourists are more likely to make purchases based on social media referrals,therefore creating tourism product awareness and its visual impact on social media acts important to capture their attention,especially during this covid-19 pandemic period. This study aims to figure out the perception of youth tourists and visual features on social media that affecting their purchase intention before visiting in a destination. This paper provides significant information for tourism products that can be brought up globally via social media platforms.